(untitled) (Acta Entomológica Chilena, 2022)
The nesting behavior of Sphex latreillei was studied in a large nesting site in Central Chile. The single cell of the nest is provisioned by the females according to the following observed pattern: nest building, paralyzing and carrying one prey into the burrow, Iaying an egg on the prey, temporary closure of the nest burrow, paralyzation and transportation of 4 - 12 new preys into the burrow and final closure.